Sociology and Methodology of Historical Research. Ethnomethodology - Konarska-Zimnicka, Sylwia (Respectus Philologicus, 2016)
The article is taking issues of the social science methodology (with particular reference to sociology, with ethnomethodology at the head) in the context of the historical research methodology. Each of the social sciences developed its own methodology that is appropriate, according to the taken research problems. However, the dialogue between these special sciences turns out to be necessary, because people are making interpretations of sources that are staying in a specific place and time and various circumstances that are accompanying them. It is probably similar to the time when those sources arose. Thus, the analysis of the source material, irrespectively to its date of coming into existence, that it would be reliable must run at various levels, including the methodology and achievements of the so-called social sciences, amongst which, from a point of view of the historian, sociology will be playing a significant role. However, ethnomethodology, which is inspecting mechanisms “making reality shared”, offers to historians a wide range of research methods, which can expand the methodology of historical research.